España en la música de Isidro Maiztegui. Herencia, ideología y migración - María Fouz Moreno (Resonancias, 2019)
The Spanish Civil War, first, and its consequences, afterwards, caused a great impact on Argentine society, especially among the artists who sympathized with it or supported the defeated. In this environment it is not strange that different Argentine composers, in some cases descendants of Spanish immigrants, would like to register their ancestry in their works as a tribute or an expression of support towards the Republicans, this is the case of Isidro Maiztegui. The decision of Isidro Maiztegui (Gualeguay, 1905 - Mar del Plata, 1996) to join in the Hispanist trend of Argentine music since the thirties is motivated by several factors, among which are his ancestry, his ideology and his relationship with the exiles and the Galician community of migrants settled in Buenos Aires. In this particular context, we are going to study the influence of the Spanish culture in the musical production of Maiztegui throughout his trajectory as composer. This influence is enriched when the composer settles temporarily in Spain in the fifties and gets in contact with the cultural reality of the country.